Cryosuction Experiments on Concrete Containing Ground Granulated Blast-Furnace Slag: Influence of Temperature, Air Entrainment And Salt - Wahlbom David; Fridh Katja (Nordic Concrete Research, 2023)
Frost deterioration of concrete is an important durability issue for structures exposed to high degree of saturation, low temperatures and de-icers. The material can then be severely damaged with internal cracking and/or scaling of the surface, which can lead to e.g. reduced protection of the reinforcement and loss of load bearing capacity. Experiments with liquid uptake in concrete using different temperature cycles was made to study cryosuction. The material used was concrete with different air content and different replacement levels of ground granulated blast-furnace slag (GGBS). The concrete samples were preconditioned by capillary suction. Three temperature conditions were used: constant temperatures of +20 °C and -20 °C, and temperature that cycled between -20 °C and +20 °C. As liquid medium, deionized water and a 3% NaCl salt solution were used. Air entrainment generally increased the liquid uptake. The amount of GGBS and the NaCl concentration in the liquid did not have any significant impact on the liquid uptake in these experiments.